Plantas geneticamente modificadas de algod??o aplicada ao controle dos insetos-praga Anthonomus grandis e Spodoptera frugiperda - Oliveira, Raquel Sampaio de (2015)
Cotton is an economically important natural fiber produced in the world and it is highly affected by insect pests and pathogens. Several transgenic approaches have been developed to improve cotton???s resistance through the expression of different transgenes, including Cry toxins, hydrolytic proteinase inhibitors, toxic peptides, dsRNA, among others. However, transformation methods remain limited by cotton variety due to the difficulties imposed by tissue culture and the steps necessary in Agrobacterium-mediated transformation and/or particle bombardment. The pollen tube transformation technique involves the introduction of an exogenous DNA into the plant genome being independent of tissue culture. This method can be applied into different cotton cultivars and it has been used successfully in generation of Bt cotton. In Chapter 2, the pollen-tube pathway technique was used to transform a Brazilian cotton cultivar. The putative transgenic plants derived from boll seeds injected with a binary expression vector, harboring the cry1Ia12 gene were initially selected with kanamycin. Selected plants were characterized using PCR, Southern blot, Western blot and ELISA techniques to confirm the genetic transformation. Western blot and ELISA data showed variable protein expression among the transgenic plants varying from 1,?? ??g g-1 to ??,??6 ??g g-1. An insect bioassay using T1 plants revealed the entomotoxic effects of Cry1Ia12 on Spodoptera frugiperda, as evidenced by a decrease in the development of insects compared with untransformed controls. Entomotoxic effect with Anthonomus grandis was also demonstrated by a decrease in the number of emerging insect adults. In Chapter 3, the agrolistic transformation technique was used to transform the Coker 310 cultivar. The putative transgenic plants derived from transformed embryos with a vector harboring the cry8Ka5 and ??AI-C3 genes were selected in vitro, and acclimatized in a greenhouse. Acclimatized plants were characterized using PCR and ELISA techniques to confirm the genetic transformation. Collected seeds from positive plants were sown for T1 plants analysis, aiming the technique evaluation. It was observed the cry8Ka5 gene amplification, and the ELISA results showed variable protein expression between transgenic plants. It was possible to demonstrate with this work, the efficacy of GM cotton plants generation using alternative biotechnological approaches, efficiently applied to the lepidopterans and coleopterans control.